Missed opportunities to address mental health of people living with HIV in Zomba, Malawi: a cross-sectional clinic survey - Kawiya, Harry Henry (Department of Psychiatry and Mental Health, 2020)
Background. Common mental disorders (CMDs), including depression and anxiety disorders, and risky alcohol use are highly prevalent among people living with HIV. Yet, many studies have found that most people who suffer from mental disorders do not receive treatment, especially in low-income countries. Given people living with HIV frequent health services, this represents a missed opportunity for identification and treatment that could improve physical and mental health outcomes. The aim of this study was to identify missed opportunities to address mental health of people living with HIV in Malawi. Four types of missed opportunities were operationalised for this study. The first two address missed opportunities for screening or identification For missed opportunity #1, a respondent had to screen positive for mental health problem (depression/anxiety or alcohol use ; and in any of their visits to the clinic in the past 12 months, the clinical officer or nurse did not ask about their mental health. Missed opportunity definition #2 was a more nuanced missed opportunity for identification of probable mental health problems. A respondent had to be undetected for mental health problems; and in any of his or her visits to the clinic in the past 12 months, the clinical officer or nurse did not ask about his or her mental health and s/he wanted to receive advice or treatment about his or her mental health problems. The second to definitions address missed opportunities for treatment. For missed opportunity definition #3, a respondent had to screen positive for mental health problem and if in any of his or her visits to the clinic in the past 12 months, and s/he did not receive advice or treatment. For missed opportunity definition #4, a more nuanced missed opportunity for the treatment of probable mental health problem: a respondent had to screen positive for a mental health problem; s/he wanted to receive advice or treatment about his or her mental health problems/alcohol use; and in any of their visits to the clinic in the past 12 months, s/he did not receive treatment for a mental disorder/risky alcohol use. Methods. A a random of participants receiving HIV care were approached while they were waiting for their consultation at three ART clinics namely: Tisungane, Matawale and Domasi. Those who consented to participants were interviewed in a private room. The Self-Reporting Questionnaire-20 (SRQ-20) and the Alcohol Use Disorders Identification Test (AUDIT) were used to detect probable cases of CMDs and clients consuming alcohol at risky levels. Following v administration of the SRQ-20 and AUDIT, participants were asked if clinical officers (COs) or nurses inquired about their feelings (sad or worried) or alcohol consumption during their routine visits to ART clinics, thus eliciting data on identification by healthcare workers or identification of CMD symptoms. The participants were also asked whether advice or treatment was recommended and whether they would have liked to receive advice or treatment regarding their feelings or risky alcohol use. Descriptive statistics were utilized to calculate prevalence estimates of missed opportunities and multiple logistic regression models were used to determine the factors associated with missed opportunities for mental health service provision. Results. The study had 382 participants. The proportion of participants who screened at risk was 77 (20.2%) for probable CMDs and 16 (4.2%) for risky alcohol use. The proportion of participants who screened at risk for any mental health problem (depression, anxiety and risky alcohol use) was 87 (22.8%). Participants who were asked by clinical officers and nurses about CMD symptoms and alcohol use were 92 (24.1%) and 89 (23.3%) respectively. Of the entire sample, 351 (91.9%) participants wanted to receive advice or treatment and 26 (29.9%) received advice or treatment. Missed opportunities to address the mental health of people living with HIV were found to be as follows: definition #1, 40 participants (46.0%); definition #2, 35 participants (40.2%); definition #3, 87 participants (100%) and definition #4, 66 participants (75.9%). After adjusting for other variables in the model female gender was significantly associated with missed opportunity definition #1. After adjusting for other variables in the model female participants were more likely to meet criteria for missed opportunity definition #2 than male participants. Furthermore, older participants were less likely to meet criteria for missed opportunity definition #2 compared to younger participants. Participants who were employed were less likely to meet criteria for missed opportunity definition #2. In the same vein, participants who were spending less were less likely to meet criteria for missed opportunity definition #2. Given all participants met criteria, we were unable to develop logistic regression models. There were no significant associations for missed opportunity definition #4. Conclusion. Approximately one fifth of the sample recruited screened at risk for CMDs and most clients wanted to receive advice or treatment. Despite over 40% of the participants reporting being asked about CMD symptoms, PHC workers did not provide advice or treatments to 75.9% of clients. There is need to advocate for screening of mental health problems including alcohol use and treatment in all ART clinics in Malawi.